Summarizing Newspaper Comments - Llewellyn, Clare; Grover, Claire; Oberlander, Jon (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
This work investigates summarizing the conversations that occur in the comments section of the UK newspaper the Guardian. In the comment summarization task comments are clustered and ranked within the cluster. The top comments from each cluster are used to give an overview of that cluster. It was found that topic model clustering gave the most agreement when evaluated against a human gold standard. This approach is compared to cosine distance clustering and k-means clustering. PageRank was found to be the prefered ranking system when compared with TF-IDF, Mutual Information gain and Maximal Marginal Relevance and evaluated against sets of comments summarized by a journalist for the Guardian letters page.